2005
DOI: 10.1364/ao.44.006419
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a Shack–Hartmann sensor for absolute measurements of wavefronts

Abstract: We demonstrate a method with which to calibrate a Shack-Hartmann sensor for absolute wavefront measurement of collimated laser beams. Nearly perfect spherical wavefronts originating from a single-mode fiber were used as references. After the calibration, the uncertainty of the wavefront was less than lambda/100 peak to valley across a diameter of 6 mm. For example, this method allowed us to balance aberrations and prepare collimated beams with wavefronts that are plane to lambda/500 across 1 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 16 publications
0
19
0
2
Order By: Relevance
“…As shown in Fig. 1(a), for the kth aperture at a distance, r k ¼ ka, from the optical axis where a is the aperture size of each microlens, the shift is related to the wavefront slope over the subaperture by [10,11] …”
Section: Theorymentioning
confidence: 99%
“…As shown in Fig. 1(a), for the kth aperture at a distance, r k ¼ ka, from the optical axis where a is the aperture size of each microlens, the shift is related to the wavefront slope over the subaperture by [10,11] …”
Section: Theorymentioning
confidence: 99%
“…In this group of sensors a trade-off is seen between high phase resolution versus high spatial resolution which is limited by the size of the lenslet-array and the number of lenses. The phase resolution that can be obtained with these sensors ranges λ/100 for an Ø6 mm beam diameter to λ/500 for Ø1 mm at λ 632.8 nm [16]. More recent research [17] showed measurement sensitivity up to λ/15500 at λ 820 nm, though the spatial resolution is again limited by a 30x30 lenslet-array over 12.5x12.5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…A WFS is essential to any AO assisted imaging system. There are a few kinds of wavefront sensing techniques including spatially resolved refractometry [9], laser ray tracing [10], Shack-Hartmann wavefront sensing [11] and pyramid wavefront sensing [12]. All these techniques sample the aberrations transversally, though none of them can provide depth resolved wavefront information.…”
Section: Introductionmentioning
confidence: 99%